A Publishing History of A Discourse of Life and Death, Translated by the Countess of Pembroke. (10th June 2021) - Moore, J K
Abstract: The short meditation, A discourse of life and death was translated by Mary (Sidney) Herbert, Countess of Pembroke in 1590 from Excellent discours de la vie et de la mort by Philippe de Mornay, seigneur du Plessis-Marly. This article presents the publishing history of Herbert's translation and how it was adapted twice in the seventeenth century. First, it is found as an incomplete manuscript by 'T. H. Gent.' (BL MS Sloane 1037). The manuscript has the correct licence to print, but the wrong author, and was used as setting copy in the print shop of George Eld and Miles Flesher in early 1624. All copies of that edition are now lost. In 1697 Herbert's translation was revised again as the 'contemplations' of Sir John Fenwick before his execution for treason.